An Unusual Cause of Pediatric Stroke Secondary to Congenital Basilar Artery Fenestration. (17th January 2013) - Gold, J. J.; Crawford, J. R.
Abstract : Basilar artery fenestration is an uncommon congenital variant that has been associated with aneurysms and posterior circulation infarcts in the adult literature. Little is known about the functional consequences of basilar artery fenestration, if any, in childhood. We present a case of a previously healthy 12-year-old boy who presented with diplopia, tinnitus, and ataxia who had subtle findings on diffusion-weighted magnetic resonance imaging consistent with posterior circulation territory infarction. Computed tomography angiography and magnetic resonance angiography revealed an area of signal abnormality in the basilar artery, which was confirmed on conventional angiography to be a type 2 basilar artery fenestration, without thrombus or aneurysm. The patient recovered from his neurologic deficits over two days and was placed on prophylactic aspirin therapy without recurrence of symptoms. This rare anatomic variant of the posterior circulation is important for physicians to recognize and may have associated neurologic consequences during childhood worthy of further investigation.